Common Errors of Level Three Students’ Writing at the English Department, Faculty of Education, Sana’a University - Almuslimi, Fazee Khalid Alezi (Journal of Curriculum and Teaching Methodology, 2023)
This research aimed to find out the common errors in third level writing at the English Department, Faculty of Education, Sana’a University during the academic year 2019-2020. It also aimed to highlight the causes of such errors. This research was quantitative research in which its results were calculated quantitatively. For the purpose of achieving the aims of the research, two data collection tools were used (an evaluation sheet for analyzing the test papers and a close ended questionnaire to highlight the errors behind the students’ errors in writing. The sample of this research was %29 of the whole population (137 participants) selected randomly to do the questionnaire (40 participants) and 20 essays booklets from the final exam papers of Advanced Writing were chosen also randomly to be as the sample of error analysis. The results showed that errors in capitalization, S-V agreement and spelling were not common because the percentage of errors was not higher than %25 The results also showed that some reasons of making errors in writing as mother tongue interference, lack of vocabulary and the traditional methods of teaching writing.